Characteristic antimicrobial resistance of clinically isolated Stenotrophomonas maltophilia CYZ via complete genome sequence. (December 2020) - Ma, Jingtao; Feng, Junhua; Shan, Yue; Zhao, Yan; Qiao, Hongxiu; Xie, Lixin; Lin, Xiaoxuan; Wang, Changle; Chuai, Xia
Highlights: Clinical Stenotrophomonas maltophilia CYZ was isolated from an immunocompromised patient. Functional annotations of the COG and GO databases revealed specific means to resist antibiotics in S . maltophilia CYZ. Phylogenetic relationship revealed that S . maltophilia CYZ was close to strains isolated from the nosocomial environment. S . maltophilia CYZ was susceptible to levofloxacin, TMP-SMX and minocycline. Abstract: Objectives: Stenotrophomonas maltophilia is an important multidrug-resistant pathogen that is associated with various serious nosocomial infections. In our study, we investigated the antimicrobial resistance traits of clinical S . maltophilia strain CYZ isolated from the sputum of an immunocompromised patient. Methods: The whole genome sequence of S . maltophilia CYZ was investigated using a PacBio RS II system. The functions of all the predicted genes were annotated by the COG, GO and KEGG databases. Several types of antibiotics were selected to test the antimicrobial susceptibility, and a phylogenetic tree was constructed based on 16S rRNA gene sequence. Results: The genome of S. maltophilia CYZ has a length of 4, 517, 685 bp and contains 4077 predicted genes, with an average G + C content of 66.65%. Functional genomic analysis via the annotations of the COG and GO databases revealed that the isolate exhibited specific means to resist antibiotics. The annotated genes involved in flagella, pili or fimbriae, biofilm formation, polysaccharide and cyclic di-GMP may contribute to promote the ability of antimicrobial resistance. This strain showed susceptibility to levofloxacin, trimethoprim/sulfamethoxazole and minocycline according to antimicrobial susceptibility testing. The phylogenetic relationship indicated that S . maltophilia CYZ was closely related to S . maltophilia strains isolated from the nosocomial environment. Conclusions: The current results give a better understanding of the genetic characteristics of antimicrobial resistance in S. maltophilia CYZ and provide a genetic basis for further study of the phenotype.